PERBEDAAN EFEKTIVITAS REBUSAN DAUN CENGKEH (Syzygium aromaticum L) DAN DAUN PANDAN (Pandanus amaryllifolius Roxb) SEBAGAI PENGUSIR LALAT RUMAH (Musca domestica) - pahruddin, muhammad; Aris Sandi, Rigo; Zubaidah, Tien (Jurnal Sanitasi Profesional Indonesia, 2022)
Abstract: Flies are vectors of foodborne diseases, among others, vomiting, diarrhea, typhoid, dysentery, and myiasis. Therefore, flies need to be controlled, one of the methods to control flies is using natural pesticides. The purpose of this study was to determine the differences in the effectiveness of decoction of clove leaves (Syzygium aromaticum L) and pandan leaves (Pandanus amaryllifolius Roxb) as a vegetable repellent for house flies (Musca domestica). This type of research was true experiment with a Posttest Only Control Group Design design. The samples in this research were the house fly (Musca domestica) with the number 315 tail and repetition 3 times. The results showed that there was a difference in effectiveness between the decoction of clove (Syzygium aromaticum L) and pandan (Pandanus amaryllifolius Roxb) leaves. With the difference power repellent repellent in the two types of repellent, namely repellent the clove leaf concentration of 40% was 91.46% and repellent pandan leaf concentration of 40% was 92.36%. From the results of this study, it is advisable for the public to use a decoction of pandan leaves (Pandanus amaryllifolius Roxb) as an repellent house fly (Musca domestica) environmentally friendly and further research can be carried out on carrier insects vector other.